2019
DOI: 10.1021/acsearthspacechem.9b00057
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Ultraviolet Photodesorption and Photofragmentation of Formaldehyde-Containing Ices

Abstract: Non-thermal desorption from icy grains containing H 2 CO has been invoked to explain the observed H 2 CO gas phase abundances in Pro-toPlanetary Disks (PPDs) and Photon Dominated Regions (PDRs). Photodesorption is thought to play a key role, however no absolute measurement of the photodesorption from H 2 CO ices were performed up to now, so that a default value is used in the current astrophysical models. As photodesorption yields differ from one molecule to the other, it is crucial to experimentally investiga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…Finally, for the specific case of CH 3 OH photodesorption, Bertin et al (2016) suggested that the UV photodesorption of methanol from pure methanol ice originates from the exothermic recombination of CH 3 O/CH 2 OH into CH 3 OH followed by its desorption (also suggested by Öberg 2016). An exothermic recombination was also proposed in similar experiments as a possible route for the UV photodesorption of H 2 CO from formaldehyde-containing ices (Féraud et al 2019). Bennett et al (2007) suggested that the main dissociation channels of CH 3 OH in condensed phase by 5 keV electrons lead to CH 2 OH, CH 3 O, and CH 4 formation.…”
Section: Mechanisms For the X-ray Photodesorption Of Neutrals From Pumentioning
confidence: 80%
“…Finally, for the specific case of CH 3 OH photodesorption, Bertin et al (2016) suggested that the UV photodesorption of methanol from pure methanol ice originates from the exothermic recombination of CH 3 O/CH 2 OH into CH 3 OH followed by its desorption (also suggested by Öberg 2016). An exothermic recombination was also proposed in similar experiments as a possible route for the UV photodesorption of H 2 CO from formaldehyde-containing ices (Féraud et al 2019). Bennett et al (2007) suggested that the main dissociation channels of CH 3 OH in condensed phase by 5 keV electrons lead to CH 2 OH, CH 3 O, and CH 4 formation.…”
Section: Mechanisms For the X-ray Photodesorption Of Neutrals From Pumentioning
confidence: 80%
“…where Y pd is the photodesorption yield (i.e., the fraction of molecules ejected over the total number of incident UV photons), G 0 is the strength of the UV photons relative to the standard interstellar radiation field. Y pd does vary on orders of magnitude from one molecule to the other (Féraud et al 2019). The timescales are shown in Figure 7.…”
Section: Ch3 Co Ohmentioning
confidence: 99%
“…The timescales are shown in Figure 7. One can see that the timescale of the rotational desorption is much shorter than that of the sublimation at T d ≤ 100 K. The thermal sublimation is dominant at T d ≥ 170 K. If we assume G 0 = U 0 = 10 5 , and adopt Y pd 7 × 10 −4 as for H 2 CO (i.e., 4-10 ×10 −4 , Féraud et al 2019), the rotational desorption mechanism is shorter than the UV photodesorption at n H < 5 × 10 6 cm −3 with 80 K ≤ T d ≤ 100 K. However, Bertin et al (2016) experimentally showed that the photodesorption yield is an order of 10 −5 for pure methanol ices, and even lower than 10 −6 when it mixes with CO molecules in the ice. In this case, the rotational desorption is dominant over the UV photodesorption.…”
Section: Ch3 Co Ohmentioning
confidence: 99%
“…pure CH 3 CN ices. Several experimental studies regarding UV photodesorption of simple molecules such as CO, CO 2 , N 2 or CH 4 (Bertin et al 2013;Fillion et al 2014;Carrascosa et al 2019;Dupuy et al 2017) and more complex molecules such as CH 3 OH and H 2 CO (Bertin et al 2016;Martín-Doménech et al 2016;Féraud et al 2019) have shown that UV photodesorption yields are strongly dependent on the ice composition: e.g., when diluted in CO-dominated ices, CH 3 OH UV photodesorption is quenched whereas H 2 CO UV photodesorption is enhanced, compared to the case of pure CH 3 OH and H 2 CO ice respectively. This indicates that the UV photodesorption of complex molecules should be systematically studied as a function of the ice composition.…”
Section: Introductionmentioning
confidence: 99%